2020
DOI: 10.1080/10410236.2020.1719321
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Physicians’ Communication Goals During Patient Interactions

Abstract: During healthcare visits, physicians may set communication goals such as providing their patient with information about treatment; however, no recommendations exist regarding which goals physicians should prioritize during their often-brief interactions with patients. Two studies examined five communication goals (providing information, reducing distress, increasing patient satisfaction, increasing patient adherence, and encouraging hope) in the context of physician-patient interactions and their relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Another study has also reported that compassionate empathy is among the most important types of interaction and relationship between the patient and health care workers in the present century (28). The success of health care workers to establish a strong relationship with a sense of empathy with patients has been reported to have a great impact on the patients' recovery, perceived self-value, distress, satisfaction, and hope (29). Also, it has been shown that patients who feel compassionate empathy from their physicians and medical staff are more successful in overcoming acute symptoms more quickly and have strengthened immune systems (30).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has also reported that compassionate empathy is among the most important types of interaction and relationship between the patient and health care workers in the present century (28). The success of health care workers to establish a strong relationship with a sense of empathy with patients has been reported to have a great impact on the patients' recovery, perceived self-value, distress, satisfaction, and hope (29). Also, it has been shown that patients who feel compassionate empathy from their physicians and medical staff are more successful in overcoming acute symptoms more quickly and have strengthened immune systems (30).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has also reported that compassionate empathy is among the most important types of interaction and relationship between the patient and health care workers in the present century (30). The success of health care workers in establishing a strong relationship with a sense of empathy with patients has been reported to have a great impact on patients' recovery, perceived self-value, distress, satisfaction, and hope (31). Additionally, it has been demonstrated that the patients who feel compassionate empathy from their physicians and medical staff are more successful in overcoming acute symptoms more quickly and have strengthened immune systems (32).…”
mentioning
confidence: 99%